O-144 Adverse pregnancy and neonatal outcomes in an oocyte donation program. Expanded Carrier Screening can substantially decrease the risk of recessive conditions. (30th June 2022) - Clua Obradó, E; Palacios-Verdú, G; Sumarroca, M; Martínez, F; Polyzos, N
Abstract: Study question: How frequent are adverse outcomes in oocyte donation (OD) programs and how many recessive conditions can be prevented with the implementation of expanded carrier screening(ECS)? Summary answer: Adverse outcomes were reported only in 1.55% of cases. ECS prevented 2.66% autosomal recessive and X-linked-conditions, interpreted in a 63% decrease in adverse outcomes. What is known already: Nowadays, oocyte donors undergo a rigorous selection process, including the evaluation of genetic risks. ECS has been widely implemented in the screening of gamete donors. Nevertheless, pregnancies conceived after OD cycles are still at risk for genetic adverse outcomes. There are very few reports in the literature regarding children born with an inherited genetic condition from a gamete donor, and they are reported in sperm donation-conceived offspring. To our knowledge, there is no published review of genetic adverse outcomes in oocyte donation offspring so far. Study design, size, duration: This is a retrospective observational study that analyses the adverse events reported in 4573 OD cycles carried out between January 2014 and December 2021 in the Reproductive Medicine Unit of Dexeus University Hospital. The study also reviews the number of high-risk assignations that has been identified in the OD program where ECS was applied to the oocyte donors and the recipient's male partner to avoid high-risk assignations. Participants/materials, setting, methods: The study includes patients who underwent OD cycles and reported an adverse outcome with a potential genetic aetiology from 2014 to 2021. Moreover, genetic matchings were revised in the OD program and high-risk assignations were defined as matchings where oocyte donors and recipients' male partners were carriers of the same autosomal recessive condition or as matchings where oocyte donor candidates were found to be carriers of X-linked conditions. Main results and the role of chance: A total of 4.573 OD cycles were performed, including 1696 oocyte donors. Seventy-one recipients (1.55%) reported an adverse outcome of the pregnancy or children born from the OD. A confirmed genetic aetiology was reported in 23 (32.4%) cases including chromosomal abnormalities, microduplications and monogenic disorders. The reported remaining cases were due to congenital malformations, stillbirth, neurodevelopmental disorders, and other conditions for which a genetic aetiology has not been established to our knowledge. Moreover, we identified 211 (4.6%) high-risk assignations due to oocyte donors and recipient's male partners being carriers of the same autosomal recessive condition when initially assigned, which would have led to an additional 1, 15% of children born with an autosomal recessive conditions (25% of 4.6% high-risk assignations). Additionally, we rejected 52 (3.07%) oocyte donor candidates that were carriers of X-linked conditions, which would have led to an additional 1.5% of children born with an X-linked disorder. Based on our results, implementation of ECS, resulted in 63% risk reduction in adverse outcomes observed in our oocyte donation program from a potential adverse event rate of 4.2% to an actual 1.55% incidence of adverse outcomes. Limitations, reasons for caution: The actual number of adverse outcomes and high-risk assignations in an OD program could be underestimated given that not all patients report the adverse outcome or in some cases adverse events have not yet developed. Additionally, the number of rejected/avoided high-risk assignations in ECS is not always collected. Wider implications of the findings: This study provides evidence that ECS reduces the probability that children born from OD could inherit some autosomal recessive or X-linked conditions. However, there are still several genetic adverse events that cannot be avoided by implementing ECS, mostly caused by de novo monogenic changes, chromosomal abnormalities, or congenital malformations. Trial registration number: Not applicable